The Efficiency of Aloe vera in inhibiting the growth of Aspergillus flavus fungus and its protective effects on growth performance and serum biochemistry of broiler chickens fed by Aflatoxin B1 - Hassan, Reda (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2023)
The study aimed to assess how well different Aloe vera gel extract (AVGE) concentrations inhibited the development of Aspergillus flavus in a potato dextrose agar (PDA) culture medium. According to the data, Aspergillus flavus growth in PDA culture medium was variably inhibited by Aloe vera gel extract at concentrations of 1, 2, 3, and 4%; these rates were 97, 100, 5.88, and 17.64%, respectively. The in vitro best concentration of AVGE was (2%). An in vivo study was conducted to investigate the protective effects of Aloe vera powder (AVP) on performance and serum biochemical parameters in broiler chickens fed on diets contaminated with aflatoxin B1 (AFB1). A total 450 broiler chicks (Ross-308) were randomly allocated to five treatments. 1) basal diet (control group), 2) contaminated diet with 1 mg AFB1/ kg diet (AFB1-diet), 3) AFB1-diet plus AVP 1g / kg diet, 4) AFB1-diet plus A 2 g / kg diet and 5) AFB1-diet plus AVP 3 g / kg diet. Each treatment consisted of six replicates of 15 birds. Growth performance was lower for groups fed 1 mg AFB1/ kg diet. At the same time, growth parameters were improved by incorporating 1 and 2 g/kg AVP in the AFB1 contaminated feed. Chicks fed AFB1 had significantly higher aspartate aminotransferase (AST), alanine aminotransferase (ALT), uric acid, and creatinine than other groups. In addition, Aloe vera powder improved biomarkers of the liver and kidney functions and reduced AFB1 residue in broilers' liver and muscle tissue. The results demonstrated that AVP at 2 g / kg diet could reduce the adverse effects of AFB1 exposure in broiler chicks.